Impact of warming temperatures on planting progress: evidence from US corn - Green, John (Kansas State University, 2022)
The impact of climate change, and the associated warming temperatures, on agricultural production has been a focus of researchers in recent years. The primary focus of many of these studies includes estimating yield losses stemming from anticipated warming temperatures. This paper quantifies the extent to which farmers adapt to warming temperatures, which leaves the door open to an extension investigating whether said adaptation could mitigate yield losses. Using USDA Crop Progress Reports, this paper analyses how planting time in US corn, specifically the median planting date, has changed over the last few decades. We find that seven of the sixteen states in our sample exhibit a statistically significant shift towards an earlier median planting date. After incorporating PRISM weather data into our models, we find a one-degree Celsius increase in average April temperature is associated with, on average, a median planting date that is 1.82 days earlier. This paper then builds upon the median planting date models by using weekly first differences in planting progress as the dependent variable, yielding a more dynamic analysis of the planting season. We allow for temporal and spatial heterogeneity in weekly weather coefficient estimates and control for realized cumulative planting progress made in previous weeks. The results indicate that warmer weekly temperatures have a positive, statistically significant impact on planting progress for the first six weeks of the planting season. Using prediction analysis, we quantify the expected impact of warmer weekly temperatures on planting progress. Results show that a one-degree Celsius increase in weekly average temperature is associated with, on average, a predicted median planting date that ranges from 0.51 days earlier in Texas to 2.08 days earlier in Kentucky.
Keywords: Production agriculture; Farmer adaptation; Climate change; Corn